Relationship between motivational climate, anxiety and average mark in pre-service physical education teachers: a cross-sectional study based on structural equation modelling approach - Eduardo Melguizo-Ibáñez; Gabriel González-Valero; Georgian Badicu; Fatma Hilal Yagin; José Manuel Alonso-Vargas; Luca Paolo Ardigò; Pilar Puertas-Molero (BMC Medical Education)
Abstract Background Motivation is a variable that directly influences task orientation. Within the motivational sphere, the motivational climate determines whether a task is performed with an intrinsic or extrinsic. Purpose It has been observed that depending on motivational orientations, anxiety levels and task performance can be increased. Likewise, there are differences in interests depending on the gender of individuals. Methods This research aims (a) To elaborate and adjust a theoretical model of the causal relationship of motivational climate on anxiety and academic performance and (b) To analyse the causal relationship between the motivational climate on anxiety and the average mark of the participants. Regarding the design, a comparative, cross-sectional and descriptive study was carried out on a sample of 558 trainee physical education teachers. The sample for this study is from southern Spain. Likewise, the branch of study of the sample is related to university degrees in education sciences and physical activity and sport sciences. The Beck Anxiety Inventory (BAI), Perceived Motivational Climate in Sport-2 and an ad hoc socio-demographic questionnaire were used to collect the data. Results It is observed that the male sex presents a greater causal relationship of task climate (β=−0.259; p ≤ 0.05) and ego climate (β = 0.324; p ≤ 0.001) on anxiety. A stronger causal relationship of task climate (β = 0.340; p ≤ 0.001) and ego climate (β = 0.241; p ≤ 0.05) on mean score is also observed for the male population. The sample presents a negative causal relationship of anxiety on the average mark. This is higher for the male population (β=−0.126). Conclusions Male students show a greater causal effect of motivational climate on anxiety and grade point average. Likewise, the causal relationship of task climate on the development of anxiety is negative for the study sample. In contrast, the ego climate exerts a positive causal relationship on the development of anxiety.